2010 IEEE Radio and Wireless Symposium (RWS) 2010
DOI: 10.1109/rws.2010.5434129
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing wireless security through reconfigurable antennas

Abstract: Applying channel information for user authentication is gaining attention in the area of wireless network security. Numerous studies have demonstrated reconfigurable antennas with multiple operating modes that have the ability to choose the best channel in a given environment. We investigate the performance gains that can be achieved by using multiple uncorrelated channel realizations for user authentication at the physical layer by employing a reconfigurable antenna. Ray tracing simulations using a reconfigur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Reconfigurable antennas are suitable for many applications especially when several operating modes are required from a single antenna. These applications include Multiple Input Multiple Output (MIMO) communication systems [1]- [9], cellular and personal communication systems [10]- [13], interference rejection [14], [15], wireless network security [16], and military applications [17]. A reconfigurable nano antenna is a reconfigurable antenna which operates in the optical range of frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Reconfigurable antennas are suitable for many applications especially when several operating modes are required from a single antenna. These applications include Multiple Input Multiple Output (MIMO) communication systems [1]- [9], cellular and personal communication systems [10]- [13], interference rejection [14], [15], wireless network security [16], and military applications [17]. A reconfigurable nano antenna is a reconfigurable antenna which operates in the optical range of frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Pattern reconfigurable antennas were demonstrated to be an important solution to improve channel capacity and security in wireless communications [1] [2]. The antenna's radiation characteristic can be changed according to the wireless channel response, improving the Signal to Noise Ratio (SNR) and consequently, the data throughput [3].…”
Section: Introductionmentioning
confidence: 99%
“…In [5]- [10], authors used RAs in MIMO systems where they showed that since RAs provide additional degree of freedom in wireless communication, their usage in MIMO increases the performance of the systems in terms of capacity or SINR. In [11], authors utilize RAs to detect intruders in the environment. Tsai et al utilized switched multi-beam directional antennas to perform the subchannel allocation in the downlink by taking consideration of the fairness in [12].…”
Section: Introductionmentioning
confidence: 99%